Development of Differentiated Digital Flipbook Teaching Materials to Enhance Sixth-Grade Students’ Mathematics Achievement - Ingka Rizkyani Akolo; Joice Pangulimang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to develop feasible, practical, and effective differentiated digital flipbook teaching materials to enhance the mathematics achievement of sixth-grade students in Madrasah Ibtidaiyah. The method used was Research and Development (R&D) with the ADDIE model covering the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 21 students, one teacher, and two expert validators. The product developed was a digital flipbook featuring videos and interactive content aligned with visual, auditory, and kinesthetic (VAK) learning styles. The results of the expert assessment showed that the teaching materials had a high level of feasibility, with 88.10% for the material and 95.83% for the media, while practicality was rated very good by the students (88.39%) and the teacher (91.67%). The small-scale and large-scale trials showed significant enhancements in learning outcomes, with an average N-Gain score of 0.6867 (moderate). These findings indicate that the differentiated digital flipbook teaching materials are considered feasible, practical, and sufficiently effective for improving the mathematics achievement of sixth-grade students